Costs of diesel pump irrigation systems in the Eastern Indo-Gangetic Plains: What options exist for efficiency gains? - Foster, Timothy; Adhikari, Roshan; Urfels, Anton; Adhikari, Subash; Krupnik, Timothy J.; International Maize and Wheat Improvement Center; International Rice Research Institute (International Food Policy Research Institute, 2019)
Groundwater irrigation plays a critical role in supporting food security, rural livelihoods and economic development in South Asia. Yet, large disparities in groundwater access and use remain across the region. In the Western Indo-Gangetic Plains (WIGP) of India and Pakistan, subsidized rural electrification and fuel for groundwater pumping has enabled significant growth in agricultural productivity over recent decades (Shah 2007). In many areas, groundwater development has however also contributed to over-extraction and aquifer depletion, especially in the WIGP (MacDonald et al. 2016; Mukherjee et el., 2017). In contrast, groundwater resources in the Eastern Indo-Gangetic Plains (EIGP) of Nepal and eastern India remain underexploited; current aggregated rates and areas of irrigation also appear to be only a fraction of estimated development potential (Saha et al., 2016). This limits farmers’ ability to grow crops outside the monsoon season, or to manage risks posed by rainfall variability and dry spells within the monsoon – both of which contribute to low productivity and rural poverty.